Pentingnya Bimbingan Islami bagi Pendidikan ditengah Kebinekaan - Moh Subhan; Abd. Haris (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2022)
Humans are social creatures. In the case of guidance in the midst of diversity, there is a relationship between two subjects, namely the guidance of subjects who guide more subjects who are less. The realization of independence and freedom from the shackles of the oppression of the colonizers until the realization of peace in the archipelago which has been recognized throughout the world for its independy ence, are noble values ??that are full of rahmatan lil'alamin which is loaded with the religion of Islam that is presented in Indonesia, Islam is present on mother earth this motherland without war and not brought by the invaders, Islam comes with hospitality and politeness as well as dialogue and culture. Islam and culture are not at all contradicted so that it is easy to be accepted by all groups, that is one way that Islam rahmatan lil'alamin enters through cultural dialogue. Islam has spread and is faced with various cultural realitifes so that this is what allows Islam to develop into a truly rahmatan lil'alamin teaching. The strength of Islamic values ??does not completely shift the strength of cultural values ??but instead enriches them. The position of Islam is able to be a guardian for the establishment of religious harmony.